Methodical recommendations for lectures and seminars from the discipline "Economic Law" for students of the DE "Bachelor" Faculty of Agricultural Management, specialty 073 "Management" - Oleksyuk, Victoria; Piddubnyi, Oleksiy (My University, 2023)
Methodical recommendations are developed for the purpose of in-depth study by students of the discipline "Economic Law", acquiring skills of independent processing of theoretical material, structuring of the necessary information. A list of recommended literature is provided.
Approved for printing by the Department of Civil Law and Economic Law of the National University of Bioresources and Nature Management of Ukraine. Approved at the meeting of the academic council of the Faculty of Law of the National University of Bioresources and Nature Management of Ukraine.
Keywords: law; Economic Law